Estudo Fitoquímico de Sclerobolium rugosum (Leguminosae) - Ferreira, Daniele Alves (2008)
This work reports the study phytochemical investigation Sclerolobium rugosum, specie of the Leguminosae family, subfamily Caesalpinoideae, a plant found on the margins of rivers in the Northeast of Brazil. There is no any scientific study about this specie, except the astringent property cited in the folk medicine. Phytochemical investigation of hexane and ethanol extracts of bark and wood of the roots of S. rugosum using silica gel allowed to isolation and identification of: Lupeol, -sistosterol and stigmasterol glycosides and one ester derivative of cinnamic acid (trans-triacontyl-4-hydroxicinnamate) (Table 01, p. X). Derivatives reactions were obtained in order to determine structures, training of the usual techniques in the laboratory and to make further studies of biological activities. Natural compounds were isolated and purified using the technique of column chromatography on silica gel (CC). The formation of derivatives reactions were accompanied by Thin-Layer Chromatography (TLC). Structure determination of natural products and derivates were done by spectrometric methods including: NMR 1H and 13C (nuclear magnetic resonance), IR (Infrared) and MS (mass spectrum). With these techniques was also possible of establish the relative configuration of compounds and derivatives.